Challenges and Ongoing Actions to Address the Mpox Emergency in Africa - Faraan O. Rahim; Mosoka Fallah; Urvish Jain; Eugene T. Richardson; Nicaise Ndembi; Ngashi Ngongo; Jean Kaseya (Annals of Global Health)
This review examines key events, challenges, and responses to the mpox public health emergency following the Africa CDC’s declaration of a Public Health Emergency of Continental Concern on August 13, 2024. In response to the crisis, over 3.6 million vaccine doses and more than $150 million in funding have been mobilized globally, with contributions from the United States, European Union, and Japan. However, challenges persist, particularly in the Democratic Republic of Congo, where a humanitarian crisis in Kinshasa has complicated mpox diagnostics and treatment. In response, the Africa CDC has deployed its One Continental Incident Management Support team, with a focus on decentralizing diagnostics and enhancing sample movement through additional PCR equipment, funded by the Pandemic Fund and USAID. To reinforce laboratory diagnostics, surveillance, and case management, the Africa CDC has adopted a comprehensive “One Team, One Plan, One Budget, One M&E” approach and has deployed 72 epidemiologists to improve data integration. Collaborative efforts with WHO, GAVI, and UNICEF aim to expedite vaccine distribution, with a target of 10 million doses by 2025, alongside enhanced vaccine safety monitoring.